FACTORS INFLUENCING CONSUMERS’ REPURCHASE INTENTION TOWARD MARTABAK ALIM CIKARANG - Roy Poan; Bima Arya Wicaksono (FIRM Journal of Management Studies, 2023)
This study aim is to analyze price perception, food quality, brand image, waiting time, towards customer satisfaction with repurchase intention as mediating factor. Quantitative methods with primary data were used in this study.  The data were collected using online survey. The data collected were analyzed with the Structural Equations modelling using Smart-PLS software. This research revealed that customer satisfaction was affected by price perception, food quality and brand image. This study was the first study that integrating price perception, food quality, brand image, waiting time towards customer satisfaction as a driver of Repurchase Intention.